2022
DOI: 10.3390/f13121969
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties Performance between Untreated and Treated with CCA Treatment at Different Age Groups of Fast-Growing Acacia Hybrid of Sarawak

Abstract: An effort was carried out to fully utilise fast-growing Acacia hybrid usage in the timber engineering field; however, the research data are still lacking. This paper aims to evaluate the physical and mechanical properties performance between untreated (control) and treated with 10% copper chrome arsenic of Acacia hybrid collected from Daikin Plantation Sdn. Bhd. Bintulu, Sarawak at air-dry condition at different age groups using the small clear method. Mechanical properties test refers to shear parallel to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…All timber planks underwent the natural air-drying process at SFC (Figure 1c). The natural air-drying process was chosen for this study to minimise strength failures such as various splits and cracks [10,20]. The timber planks had to achieve the permissible air-dry moisture content (MC), which is ±19% before performing further laboratory procedures, and it takes approximately one year to achieve that moisture content condition.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…All timber planks underwent the natural air-drying process at SFC (Figure 1c). The natural air-drying process was chosen for this study to minimise strength failures such as various splits and cracks [10,20]. The timber planks had to achieve the permissible air-dry moisture content (MC), which is ±19% before performing further laboratory procedures, and it takes approximately one year to achieve that moisture content condition.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Hence, the timber sticks were marked according to mechanical testing: static bending (MOR and MOE), compression parallel to the grain, and shear parallel to the grain. The most suitable method suggested in the literature for testing timber samples is using the defect-free or small-clear sample method [10,21,22]. The samples were prepared in accordance with BS 373 [23].…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study [8] aimed to expand the fast-growing Acacia hybrid usage in the timber engineering field by using copper chrome arsenic (CCA) treatment. It was found that the treated samples in the tangential direction performed better than the untreated samples, while the radial direction gave a high average strength increment when treated.…”
mentioning
confidence: 99%